2021
DOI: 10.24018/ejbmr.2021.6.3.849
|View full text |Cite
|
Sign up to set email alerts
|

Brain Drain in Higher Education. The Impact of Job Stress and Workload on Turnover Intention and the Mediating Role of Job Satisfaction at Universities

Abstract: This study seeks to determine the impact of job stress and workload on turnover intention along with the mediation role of job satisfaction. A total of 140 academics and management personnel participated in this study’s survey. A partial least square structural equation modeling was used for data analysis. The results show that job stress and workload have a positive effect on turnover intention, while job satisfaction mediates the relationship between job stress, workload, and turnover intention. Future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 50 publications
3
33
0
3
Order By: Relevance
“…According to the conservation of resource theory, personal resources are limited, if work for a long time consumes resources that are allocated for the family, it will makes teachers feel under pressure and causes dissatisfaction with their work at school ( 54 , 55 ). Studies have shown that work-family conflict is a source of stress, and they can lead to turnover intention ( 56 , 57 ). Therefore, work-family conflict can positively affect turnover intention, and the stronger the work-family conflict, the stronger the turnover intention of teachers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the conservation of resource theory, personal resources are limited, if work for a long time consumes resources that are allocated for the family, it will makes teachers feel under pressure and causes dissatisfaction with their work at school ( 54 , 55 ). Studies have shown that work-family conflict is a source of stress, and they can lead to turnover intention ( 56 , 57 ). Therefore, work-family conflict can positively affect turnover intention, and the stronger the work-family conflict, the stronger the turnover intention of teachers.…”
Section: Discussionmentioning
confidence: 99%
“…While specifying the literature on the Pakistani context, WPS has been observed in various sectors e.g. Armed forces, educational, medical and services sectors (Malik and Naeem, 2011; Noor and Arif, 2011; Zafar, 2010), but again the adaptive performance has been predicted through leaders’ self-efficacy, emotional intelligence and training (Anees et al , 2020; Munir et al , 2020), but organizational determinants like WPS have been ignored.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Consequently, many nurses intend to quit their organizations ( Potter, 2006 ; Adriaenssens et al, 2015 ; Shah et al, 2021 ). Studies on nursing have shown a strong association between job stress and nurses’ turnover intentions, arguing that job stress actually triggers nurses’ turnover intentions ( Gates et al, 2011 ; Anees et al, 2021 ; Shah et al, 2021 ). This notion is supported by other research studies where job stress has been found to activate emotional exhaustion, which includes a negative self-concept and work attitude, resulting in a loss of interest in patients and increased turnover intentions ( Sonnentag et al, 2010 ; Lapointe et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%